Assessment Of Hazard Problems In Workplace Related To Emergency Response Plan For Employees In Primary Health Care Centers At Babylon City. - Hussein Kadhim Abbood (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The study titled